Does a Cosmic Ether Exist? Evidence from Dayton Miller and Others - DeMeo, James (Journal of Scientific Exploration, 2014)
The author reviewed the experimental ether-drift experiments and publications of Michelson-Morley, Dayton Miller, Michelson-Pease-Pearson, and more recent others, from the late 1800s through the present. Many of these historical studies presented positive results in detecting a cosmic ether, and ether-drift through space. Among these experiments, the most widely cited Michelson-Morley experiment of 1887, which did show a slight positive result (and never the claimed "null"), was found to be the least significant or robust in terms of experimental procedures and actual data collected, as compared with the far more important 1920s' study by Miller on Mount Wilson near Los Angeles, California. Most ether-drift experiments yielding claimed negative results were plagued by various unwarranted assumptions about the capacity of an ether-drift to penetrate dense materials such as stone buildings or metal shielding, or that ether flow would "contract" matter, including measuring instruments, leaving the ether-drift undetectible. Some obtained positive results, but the authors chose to interpret them as "negative" due to unwarranted assumptions demanding extremely fast ether-drift velocities near to the Earth's surface. Miller was the first to experimentally account for these issues, his most important study made atop Mount Wilson in a thermal shelter, with the largest light-beam interferometer ever constructed, and where the light-beam path was enclosed only by light glass or cardboard. His procedures accounted for a matter-retarded cosmic ether-drift with a reduced velocity closer to the Earth's surface. Miller thereby obtained significant positive results over four epochs of study. Albert Einstein also was aware of these issues, and admitted openly that if Miller was correct, then his own relativity theory would "collapse like a house of cards." In subsequent years, however, the followers of Einstein defeated this evidence for the cosmic ether by public ridicule and political tactics, not too different from the modern "skeptic" movement. The Shankland, McCuskey, Leone, and Kuerti article claiming to have reviewed Miller's Mount Wilson data, well after all the old ether-drift experimenters were dead and could no longer defend their findings, were also specifically reviewed and found to not support their own stated conclusions, thereby leaving the question of a cosmic ether and ether-drift as an open and unresolved question, or one which positive evidence indicates has been proven out. More recent ether-drift experiments from the last quarter of the 20th and early 21st Centuries, notably by Galaev, Múnera, and others, using radiofrequencies, light-beam interferometery, and other novel methods, have provided further proof for the existence of a cosmic ether in space.